2003
DOI: 10.1023/a:1023785200638
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An increase in the size and cellularity of duodenal crypts and a decreased incidence of bifurcating crypts is observed in response to very short-term feeding of a riboflavin-deficient diet to weanling rats. A study was conducted to determine whether the absence of riboflavin in the lumen of the small intestine impairs gastrointestinal development. Forty-eight female weanling Wistar rats were allocated to one of two treatment regimens, to receive either a riboflavin-deficient diet and a daily intraperitoneal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Lack of riboflavin inhibits normal increase of villus, thus affecting the function of villus (Yates et al, 2003). In the current study, piglets fed diets with low riboflavin content showed decreased duodenal VH.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Lack of riboflavin inhibits normal increase of villus, thus affecting the function of villus (Yates et al, 2003). In the current study, piglets fed diets with low riboflavin content showed decreased duodenal VH.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies report that lack of riboflavin in the diet, affects normal development process of pigs (Williams et al, 1996b;Yates et al, 2003). Frank et al (1988) reported that lack of riboflavin during lactation can lead to a significant reduction in feed intake and weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, riboflavin is also required for the postnatal development of the gastrointestinal tract. Its deficiency was associated with crypt hypertrophy, interruptions in crypt bifurcation in rats [37,38], and loss of proliferative potentials in intestinal cells [39]. These changes were seen in the postnatal and post-weaning stages [38].…”
Section: Vitamin B2/riboflavinmentioning
confidence: 99%